USING QUANTUM LEARNING METHOD IN TEACHING READING COMPREHENSION OF GRADE TENTH STUDENTS OF MAN 1 KOTA PALU - Dg Siame, Widya Khairunnisa; R Mertosono, Sudarkam; Wahyudin (English Language Teaching Methodology, 2025)
The objective of the study is to find out the effectiveness of the using of quantum learning method in teaching reading comprehension of the grade tenth students of MAN 1 Kota Palu in the academic year 2024/2025. This pre-experimental research involved a sample of grade tenth students of MAN 1 Kota Palu which consisted of 19 students chosen by using the purposive sampling technique. The data were collected by using pre and post test. The data were analyzed by using statistical methods. This findings revealed a significant improvement in the student’s reading comprehension. It was proved by the result of the t-counted (4.25) which was greater than the t-table (1.734) in the significance degree, (0.05). The conclusion of this research indicates that the using quantum learning method is effective in teaching reading comprehension in the classroom and provides a significant effect to improve the student’s level of reading comprehension.